ANALISIS PENGGUNAAN AI DALAM PEMBUATAN BAHAN AJAR PENDIDIKAN PANCASILA DI SD NEGERI 1 BEBALANG - Handayani, Ni Wayan Riska; I Nyoman Sudirman; Desak Putu Anom Janawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in Artificial Intelligence (AI) offer new opportunities for teachers to improve the efficiency and quality of instructional material development. However, the use of AI in developing Pancasila Education instructional materials at the elementary school level still faces various challenges. This study aims to analyze the implementation of Artificial Intelligence (AI) in the development of Pancasila Education teaching materials and to identify obstacles and solutions regarding its use at SD Negeri 1 Bebalang. This study employs a qualitative descriptive approach, involving one Pancasila Education teacher as the research subject. Data were collected through observation, semi-structured interviews, and analysis of teaching modules. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, while data validity was tested using source triangulation and methodological triangulation. The results indicate that AI assists teachers in formulating learning objectives, designing learning activities, developing instructional media, and creating assessments more efficiently. However, the outputs generated by AI still require validation and adaptation to the curriculum and student characteristics. Challenges identified include AI outputs that do not fully align with learning needs, difficulties in crafting effective prompts, limited internet connectivity, and the absence of guidelines for AI use at the school. These challenges were addressed by refining prompts, validating AI outputs, utilizing alternative learning resources, and enhancing teachers’ competencies. Thus, AI has the potential to serve as a supportive technology in the development of instructional materials when used critically, ethically, and responsibly.